Search for new physics in lepton+photon+X events with 305pb-1 of pp̄ collisions at s=1.96 TeV - Abulencia, A; Acosta, D; Adelman, J; Affolder, T; Akimoto, T; Albrow, MG; Ambrose, D; Amerio, S; Amidei, D; Anastassov, A; Anikeev, K; Annovi, A; et al. (2006)
We present results of a search for anomalous production of events containing a charged lepton (l, either e or μ) and a photon (γ), both with high transverse momentum, accompanied by additional signatures X, including missing transverse energy (ET) and additional leptons and photons. We use the same selection criteria as in a previous CDF search but with a substantially larger data set, 305 pb-1, a pp̄ collision energy of 1.96 TeV, and the CDF II detector. We find 42lγET events versus an expectation of 37.3±5.4 events. We observe 31 γ+X events versus an expectation of 23.0±2.7 events. We find no events similar to the run eeγγET event. © 2006 The American Physical Society.